HUBUNGAN STATUS GIZI DENGAN MORBIDITAS ISPA ANAK USIA BALITA DI DESA TANJUNG TANAH KECAMATAN DANAU KERINCI KABUPATEN KERINCI - ASMIDAYANTI, SUSI; Kasmita, Kasmita; Yuliana, Yuliana (Journal of Home Economics and Tourism, 2012)
This research aims : 1.To describes State of nutrition. 2. To knowmorbidity of ISPA and 3. To analyze the relationship of nutrition state and ISPAmorbidity of children at Tanjung Tanah district of Kerinci. Kind of this researchis descriftive quantitative with correlational approach. The population of thisresearch are the children at Tanjung Tanah district 1-5 years old about 41children with 41 samples. The technique of data collection was done by usingdirect measurement of body weigh and heigh. And the technique of ISPA mobilitycollection was done by using questioner and interviews. Base on the result of theanalysis of this research there were found three result: there were many childrenof Tanjung Tanah Kecamatan Danau Kerinci Kabupaten Kerinci district facedpoor nutrition state. The average of ISPA morbidity happened during 27.59 dayswithin six last months. Thirdly the relationship of children nutrition state withTanjung Tanah village with negative correlative of ISPA mobility collection (r=0.619) with significant and strong relationship. Base on the result its concludedthat if someone possesses good nutrition state therefore the conditions of ispamorbidity decrease and vice versa.